Shade-tree biomass and ecosystem services remain stable over 8 years in cocoa agroforestry systems in Bahia, Brazil - Sofía G. Montalvo-Yánez; Daniel Piotto; Florencia Montagnini; Simon A. Queenborough (Agroforestry Systems, 2026)

Recovery of secondary forest following selective timber harvest in the Brazilian Atlantic Forest - Daisy Christiane Zambiazi; Alfredo Celso Fantini; Daniel Piotto; Alexandre Siminski; Alexander Christian Vibrans; Ilyas Siddique; Geferson Elias Piazza; Marielos Peña-Claros (Forest Ecology and Management, 2026)

Aboveground biomass variation in working landscapes of Southern Bahia, Brazil - Janaine Isabela da Silva Rocha; Daniel Piotto (Environment, Development and Sustainability, 2026)
Native tropical forests have been increasingly replaced by different land uses. But some of these lands have regrown into secondary forests and agroforestry systems, among other forest cover types. Understanding how different forest cover types contribute to aboveground biomass (AGB) in working landscapes is central to policy and resource management, given the increasing transformation of tropical landscapes. Here, we used Generalized Linear Models (GLM) to compare aboveground biomass in different forest covers, as follows: secondary forests of 10-year-old, 25-year-old and 40-year-old, mature forests and two different agroforestry systems (AFS): ‘cabruca’ and ‘conventional’. Our results showed that the cocoa production areas in the cabruca system (106.07 Mg/ha) have similar AGB compared to 40-year-old secondary forests (159.67 Mg/ha), but the mature forests (391.65 Mg/ha) stored the highest amount of AGB compared to other forest covers. We emphasize the importance of mature forests for carbon storage, in addition to maintaining various ecosystem services. In addition, we demonstrate that agroforestry systems are very important for the storage of AGB in working landscapes, with values similar to secondary forests in an advanced stage of development. Furthermore, we stress the importance of working landscapes that include agroforestry systems and secondary forests, as they provide timber and non-timber products, reduce the pressure on native forest resources, and contribute to the provision of ecosystem services, such as carbon storage. Our results also highlight the potential of southern Bahia for the implementation of carbon credit projects that include natural forests and other forest cover types.

Reforestation strategies integrating tropical timber production can offset costs and finance forest restoration in the Brazilian Atlantic Forest - João Paulo Bispo Santos; Pedro Henrique Santin Brancalion; Mark S. Ashton; Florencia Montagnini; Claudia Fontana; Allana Katiussya Silva Pereira; Mário Tomazello-Filho; Vinicius Castro Souza; Daniel Piotto; Ricardo Ribeiro Rodrigues (Forest Ecology and Management, 2026)

Age trends in Bertholletia excelsa Bonpl. progeny test reveals high early selection efficiency and support genetically-oriented thinning management - Andrei Caíque Pires Nunes; Samir Rolim; Daniel Piotto (New Forests, 2026)

Diameter growth models and performance of 100 tropical tree species in silvicultural trials in Brazil - Samir G. Rolim; Daniel Piotto (Forest Ecology and Management, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Forestry in the Face of Global Change: Results of a Global Survey of Professionals - Austin Himes; Jürgen Bauhus; Shankar Adhikari; Saroj Kanta Barik; Hugh Brown; Andreas Brunner; Philip J. Burton; Lluís Coll; Anthony W. D’Amato; Jurij Diaci; Yonten Dorji; Ernest G. Foli; et al. (Current Forestry Reports, 2023)
Purpose of Review Forests support most global terrestrial biodiversity and contribute to the livelihood of billions of people, but these and other benefits are in jeopardy due to global change. This leads to questions, such as how to address the challenges of global change in forest management, given the lack of knowledge and deep uncertainty about future developments. In addition, many of the impediments to implement adaptation strategies are unknown. Recent Findings Here, we present an overview of results from a global survey of 754 forestry professionals (370 researchers and educators, 227 practicing foresters, 37 policymakers, 64 administrators, and 56 with other or unspecified roles) from 61 countries across 6 continents who were interested in global change issues. These professionals were asked about their opinion regarding three different adaptation strategies: resist , adapt , and transform . Most respondents agreed that the majority of global change factors will negatively influence the ability of forests to provide desired ecosystem services. Similarly, they agreed about major challenges when implementing adaptation strategies and specifically whether our current knowledge base is sufficient. These concerns were not limited to ecological aspects, but respondents also highlighted the need for a better appreciation of social/political and economic barriers, especially regarding transformation strategies. In addition, the response patterns, including differences due to economic status, highlight the importance of developing and evaluating adaptation strategies in a local social–ecological context. Summary Our study demonstrates a widespread perception on the part of forestry professionals around the world, especially among researchers and practitioners, that many global change factors will affect sustainable forest management negatively, resulting in the need for active silvicultural adaption. The results also suggest potential barriers to different adaptation strategies, particularly a relative lack of information and social acceptance for transform strategies. Further, this study highlights the importance of social and political factors and the need to understand the general public’s values regarding adaptation strategies as well as how the influence of public opinion is perceived by forest managers.

Property size and forest cover were key determinants of forest restoration in Southern Bahia in the Atlantic Forest of Brazil - Rayna Benzeev; Ashton Wiens; Daniel Piotto; Peter Newton (Land Use Policy, 2023)

Nearby mature forest distance and regenerating forest age influence tree species composition in the Atlantic forest of Southern Bahia, Brazil - Daniel Piotto; Luiz Fernando Silva Magnago; Florencia Montagnini; Mark S. Ashton; Chadwick Oliver; William Wayt Thomas (Biodiversity and Conservation, 2021)

Cadmium toxicity and its relationship with disturbances in the cytoskeleton, cell cycle and chromosome stability - Daniel Pizzaia; Marina Lima Nogueira; Mateus Mondin; Marcia Eugenia Amaral Carvalho; Fernando Angelo Piotto; Millor Fernandes Rosario; Ricardo Antunes Azevedo (Ecotoxicology, 2019)

Cadmium exposure triggers genotype-dependent changes in seed vigor and germination of tomato offspring - Marcia Eugenia Amaral Carvalho; Fernando Angelo Piotto; Marina Lima Nogueira; Francisco Guilhien Gomes-Junior; Helena Maria Carmignani Pescarin Chamma; Daniel Pizzaia; Ricardo Antunes Azevedo (Protoplasma, 2018)

Silvicultural and economic aspects of pure and mixed native tree species plantations on degraded pasturelands in humid Costa Rica - Daniel Piotto; Dylan Craven; Florencia Montagnini; Federico Alice (New Forests, 2010)

Forest recovery after swidden cultivation across a 40-year chronosequence in the Atlantic forest of southern Bahia, Brazil - Daniel Piotto; Florencia Montagnini; Wayt Thomas; Mark Ashton; Chadwick Oliver (Plant Ecology, 2009)